Evaluation of the sexual performance of female nursing undergraduate students: DOI: 10.15343/0104-7809.200832.4.3 - Santos Marques da Fonseca, Maria Fernanda (2008)
The objective of this work was to evaluate the sexual function female nursing undergraduate students. It is a descriptive –exploratory and prospective study using the resources of the quantitative approach. The population of the present study was composedby 167 female nursing graduate students and to whom we applied demographic-partner prepared by the authors was applied the FemaleSexual Function Index (FSFI) and a social-demographic questionnaire created by the authors. The age group of students was 17-39years, with an average of 23.4, a mean of 24.5 and a standard deviation of 7.8. As for marital status, 92.2 % of the students were single.Regarding sexual function, 40.8 % of the students referred a regular to good sexual performance. We conclude from the study that thepattern of sexual performance of nursing female graduate students is appropriate. However, we detected that a group of students hasan unfavorable pattern of sexual performance.